HUBUNGAN TIPE KEPRIBADIAN DENGAN BURNOUT PADA MAHASISWA TAHUN PERTAMA PSSIKPN FK UNUD - Ni Made Mega Indah Sari; Gusti Ayu Ary Antari; Ida Arimurti Sanjiwani (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
The nursing students are one of the groups that are susceptible to get stress. Uncontrolled and long-term stress could cause negative impacts, like as burnout. One of the factors that can affect burnout is personality type. Personality type are able to determine the reaction caused by stress which is impacting burnout. The aim of this study was to find out the relationship between personality type and burnout in first year nursing students of Udayana University. This study was a correlational analysis research with 70 students as the samples which was obtain by simple random sampling technique. Big Five Inventory (BFI) and Maslach Burnout Student Survey (MBI-SS) questionnaires were used as the measuring instrument. Pearson Product Moment and Spearmen Rank statistical tests were used as data analysis. The analysis result showed that based on personality type most of the respondents were in the dimension of neuroticism (67.1%). A total of 7.1% of respondents have a high category of burnout, 90.0% respondents have moderate category of burnout, and 2.9% of respondents have low category of burnout. The test analysis indicated that there was found a low positive relationship between neuroticism and burnout in first year nursing students (p = 0,041; r = 0,245). However, no significant relationship was found between openness to experience, conscientiousness, extraversion and agreeableness to burnout in first year nursing students. According to the above results, it can be concluded that personality type can be related to burnout in first year nursing students. It is highly recommended that nursing institution to develop an orientation program associated with personality type and implement a strategy to prevent burnout in students.